2004
DOI: 10.1074/jbc.c300557200
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated Protein Kinase Plays a Role in the Control of Food Intake

Abstract: AMP-activated protein kinase (AMPK) is the downstream component of a protein kinase cascade that actsas an intracellular energy sensor maintaining the energy balance within the cell. The finding that leptin and adiponectin activate AMPK to alter metabolic pathways in muscle and liver provides direct evidence for this role in peripheral tissues. The hypothalamus is a key regulator of food intake and energy balance, coordinating body adiposity and nutritional state in response to peripheral hormones, such as lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
567
2
16

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 686 publications
(614 citation statements)
references
References 28 publications
29
567
2
16
Order By: Relevance
“…There is also widespread agreement that treatments which activate AMPK in the hypothalamus, such as infusion with the nucleoside 5-aminoimidazole-4-carboxamide riboside, treatment with the gut hormone ghrelin or cannabinoids, or hypoglycaemia, all increase food intake in rodents (30)(31)(32) .…”
Section: Regulation Of Amp-activated Protein Kinase By Adipokines Andmentioning
confidence: 99%
“…There is also widespread agreement that treatments which activate AMPK in the hypothalamus, such as infusion with the nucleoside 5-aminoimidazole-4-carboxamide riboside, treatment with the gut hormone ghrelin or cannabinoids, or hypoglycaemia, all increase food intake in rodents (30)(31)(32) .…”
Section: Regulation Of Amp-activated Protein Kinase By Adipokines Andmentioning
confidence: 99%
“…2,3 We and other laboratories have shown that hypothalamic AMPK plays a major role in the regulation of organism's energy balance. [4][5][6] Our interest in hypothalamic AMPK grew from our work with C75, a synthetic molecule that inhibits fatty acid synthase (FAS) 7 and stimulates carnitine palmitoyltransferase-1 (CPT-1) and beta-oxidation of fatty acids. [8][9][10] Fatty acid metabolic pathways are poised at a crossroads of energy deficit and energy surplus, with the potential to either use or make the high-energy molecule ATP.…”
Section: Introductionmentioning
confidence: 99%
“…2,31 Hormones and pharmacological agents modulate AMPK activity in muscle, liver and hypothalamus to promote fatty acid oxidation, glucose utilization and feeding responses. [4][5][6]36,37 Physiological stimuli can activate AMPK to promote tissue-specific responses such as skeletal muscle glucose uptake and glycolysis through glucose transporter translocation and 6-phosphofructo-2-kinase kinase activity, respectively, and fatty acid oxidation. 32,33,38 Liver AMPK inhibits fatty acid and cholesterol biosynthesis by phosphorylating and inactivating ACC and 3-hydroxy-3-methylglutaryl-coenzyme A reductase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that administration of ghrelin to rats affects AMPK activity, although this effect is tissue-specific. In the hypothalamus, central and peripheral ghrelin treatments enhance protein levels of AMPK and this activation and alterations on lipid metabolism mediate the Page 17 of 37 A c c e p t e d M a n u s c r i p t 17 orexigenic effects of ghrelin (Andersson et al 2004;Kohno et al 2008;Kola et al 2005Kola et al , 2008Lopez et al 2008). In fed animals peripheral chronic and acute ghrelin treatments provoked AMPK activation in the heart, while in liver and adipose tissue it was inhibited and no effect was detected on skeletal muscle (Barazzoni et al 2005;Kola et al 2005).…”
mentioning
confidence: 99%